Gurutta Junaid Sulaeman’s Political Hijrah: From Fundamental to Moderate Islam - Alimin Alimin; Fahmi Gunawan; Muslihin Sultan; Muh. Subair (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2021)
Albeit the research into Junaid Sulaeman as the most famous Islamic Cleric in South Sulawesi was extensively undertaken, little empirical research addressed his political biography. This research aimed to explore his political Hijrah from Islamic fundamentalism to Islamic moderate. This research adopted a biography study design. To collect data, a documentary analysis based on Junaid Sulaeman’s diary and in-depth interview were conducted. The data analysis was carried out thematically using Azra’s and Al-Jauhari’s concept of fundamental and moderate Islam. The research revealed three findings. First, Junaid Sulaeman’s political Hijrah was conducted from Darul Islam toward Golongan Karya party. Second, the factors that drove Junaid Sulaeman’s participation in the political movement included the changing of socio-political context, the breadth and depth of his religious knowledge, the need to get Allah's guidance, and the consideration of dawah. Third, the implications of Junaid Sulaeman's political movement were known from the expansion of his local and national network, as well as the development of socio-religious institutions in Bone. The research concluded that a good cooperation between the ulama and the government could provide more benefits and blessings to the community.